PROBLEMATIQUE DE L’ORGANISATION SCOLAIRE DES ECOLES PRIVEES AGREEES DE LA COMMUNE DE LIMETE DANS LA VILLE DE KINSHASA - Kadiombo Bujika Marie Chantal,; Operusurusi Ondao Solange, (IJRDO - Journal of Social Science and Humanities Research, 2024)
This research focuses on “the problem of the educational organization of approved private schools in the commune of Limete in the city of Kinshasa.” the hierarchical knowledge of the organization and management of approved private schools of the heads of establishments in relation to good school organization, proves that only 23.1% of the subjects surveyed have a “very good” knowledge of the functions played by the hierarchical structures vis-à-vis approved private schools; while the majority of subjects, i.e. 53.8% of our sample, have “average” knowledge of these roles; and above all the study revealed that a good number of school heads, i.e. 23%, are unaware or barely know the functions of hierarchical authorities.In relation to knowledge of official documents governing private education, we observed that 62.4% of school heads have either average or insufficient knowledge of these documents. Above all, the study shows that 29.8% of school heads have insufficient knowledge of the sanctions provided for schools which do not follow official instructions. Only 7.8% are very familiar with the planned sanctions.